2019
DOI: 10.1101/845263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of both mutant and wild-type RAS-GTP in KRAS G12C colorectal cancer through cotreatment with G12C and EGFR inhibitors

Abstract: Multiple KRAS G12C inhibitors are in development, and the identification of effective combination treatment regimens should maximize the benefit these agents have on cancer patients. Here, we find that KRAS G12C heterozygous mutated colorectal cancer cells are sensitive to targeting with EGFR therapeutic antibodies. We find that KRAS G12C is partially impaired in binding to tumor suppressor NF1 and also to RAF, and our computational simulations reveal how these deficiencies result in partial sensitivity to EGF… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(140 reference statements)
0
3
0
Order By: Relevance
“…The ErbB receptor family is composed of four members: ERBB1/EGFR, ERBB2/ HER2, ERBB3/HER3 and ERBB4/HER4, which mainly activate MAPK and PI3K-AKT signaling pathways. High EGFR promotes RAFi resistance in CRC, lung, melanoma and thyroid cancer cells by rapid feedback activation of EGFR signaling [113][114][115][116][117], and determines the G12Ci refractory state in KRAS G12C cancers [33,34,[118][119][120]. However, EGFR does not seem to be the dominant driver of MEKi resistance in PDAC.…”
Section: Receptor Tyrosine Kinasesmentioning
confidence: 99%
“…The ErbB receptor family is composed of four members: ERBB1/EGFR, ERBB2/ HER2, ERBB3/HER3 and ERBB4/HER4, which mainly activate MAPK and PI3K-AKT signaling pathways. High EGFR promotes RAFi resistance in CRC, lung, melanoma and thyroid cancer cells by rapid feedback activation of EGFR signaling [113][114][115][116][117], and determines the G12Ci refractory state in KRAS G12C cancers [33,34,[118][119][120]. However, EGFR does not seem to be the dominant driver of MEKi resistance in PDAC.…”
Section: Receptor Tyrosine Kinasesmentioning
confidence: 99%
“…Evidence for this possibility comes from statins, HMG-CoA reductase inhibitors, which inhibit the mevalonate pathway by directly interfering with farnesylation processes [188]. In vitro trials using CRC cells did show a synergis-tic effect when statins and EGFR monoclonal antibody were combined [189], but their use in clinical trials did not restore the sensitivity to cetuximab in patients harbouring RAS mutations [190].…”
Section: Anti-ras Strategies: a New Ally For Improving Current Efgr-targeted Therapies?mentioning
confidence: 99%
“…Recently, a preclinical study has suggested synergism between cetuximab and AMG 510 in KRAS G12C mutated CRC, implying that the combination could be explored as an alternative approach. 79 Meanwhile, one can explore the upcoming results of different KRAS G12C inhibitors, as well as mutant-specific agents targeting more common variants such as KRAS G12D or G12V. 80 treating patients with rare genetic alterations Other than BRAF or HER2, even rarer genetic alterations in mCRC are now being considered as actionable targets.…”
Section: Strategies Targeting Braf-mutant Crcmentioning
confidence: 99%